Durvalumab induced immune-related agranulocytosis after conversion surgery in a patient with intrahepatic cholangiocarcinoma: a case report - Kitamura, Yoshihito; Shimizu, Seiichi; Kuroda, Shintaro; Honmyo, Naruhiko; Nakano, Ryosuke; Sakai, Hiroshi; Tahara, Hiroyuki; Ohira, Masahiro; Ide, Kentaro; Kobayashi, Tsuyoshi; Ichinohe, Tatsuo; Ohdan, Hideki (Frontiers in Immunology, 2025)
We report a rare hematological immune-related adverse event (irAE) induced by durvalumab, an immune checkpoint inhibitor, after conversion surgery in a patient with intrahepatic cholangiocarcinoma (ICC). A 72-year-old male was admitted for recurrent ICC treatment in the posterior sector. The primary treatment chosen was systemic chemotherapy with durvalumab combined with gemcitabine and cisplatin. After eight cycles of chemotherapy, partial hepatectomy was performed against three nodules of ICC at liver segments 6 and 7 as conversion surgery. Approximately 3 months after the last injection of durvalumab, the patient was readmitted to our department due to a high fever. The number of neutrophils dropped to zero. Despite daily administration of granulocyte colony-stimulating factor, the patient had agranulocytosis with neutrophil counts remaining between 0 and 80/µL for 16 days. The results of the bone marrow biopsy indicated that the patient had cytotoxicity due to autoimmunity against the common progenitor cells of granulocytes and monocytes as an adverse reaction to durvalumab. The patient was diagnosed with immune-related neutropenia and started on steroid bolus therapy. Four days after initiating steroid therapy, the neutrophil count began to improve, reaching 1540/µL after 7 days, and remained stable thereafter. This case highlights the potential for durvalumab-induced immune-related agranulocytosis following conversion surgery in a patient with ICC, emphasizing the importance of careful monitoring and timely management of irAEs, particularly in the context of postoperative infections.